1983
DOI: 10.1111/j.1365-2621.1983.tb09155.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rigor‐State, Levels of Salt and Sodium Tripolyphosphate on Physical, Chemical and Sensory Properties of Frankfurter‐Type Sausages

Abstract: Preblends of prerigor or postrigor pork with 2 or 4% salt were used to make sausages with finished product salt contents of 2.5 or 1.5% and with or without sodium tripolyphosphate. pH values increased (P > 0.001) when sausages were made with preblends of 4% salt or when phosphate was used. Reducing salt contents from 2.5 to 1.5% did not (P < 0.05) affect physical, chemical or sensory properties except for saltiness and In&on force of rupture values. Firmness of sausages increased (P < 0.05) when sodium tripoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 4 publications
2
32
0
Order By: Relevance
“…Others have shown increased product firmness and hardness with the addition of phosphate (Puolanne and Terrell, 1983;Jantawat and Carpenter, 1989). Cohesiveness was highest in the BK-K and BK-450 treatments (PϽ0.05).…”
Section: % Fat/20% Water-added Frankfurtersmentioning
confidence: 91%
“…Others have shown increased product firmness and hardness with the addition of phosphate (Puolanne and Terrell, 1983;Jantawat and Carpenter, 1989). Cohesiveness was highest in the BK-K and BK-450 treatments (PϽ0.05).…”
Section: % Fat/20% Water-added Frankfurtersmentioning
confidence: 91%
“…4 The chloride ion is thought to be responsible for the effect of NaCl on the myofibrillar proteins because it interacts strongly to neutralize the positive charges on the muscle proteins, while the sodium ion is only weakly bound. 4 -2946102109 - 128 In addition, Hamm 62 had indicated that the chloride ion was responsible for the myofibrillar swelling caused by NaCl. Nuclear magnetic resonance (NMR) studies have also found that the Cl~ ion causes myofibrillar repulsion irrespective of the cation involved.…”
Section: The Physical Entrapment Theorymentioning
confidence: 99%
“…The agitation of flaked meat particles in the presence of salt and phosphates enhances the extraction of the salt-soluble proteins to bind adjacent meat surfaces. Salt and phosphates may be added to preblends and to meat batters during chopping (Puolanne and Terrell, 1983). Phosphates enhance water binding capacity (Hamm, 1970), and their use in restructured steaks may increase the water binding capacity in blends with low salt content.…”
Section: Introductionmentioning
confidence: 99%
“…The use of phosphates may improve sensory and visual properties in restructured steaks and result in a product which resembles intact muscle in textural properties. Sodium tripolyphosphate (STP) has been studied (Puolanne and Terrell, 1983;Matlock, 1983) but has not been compared to sodium acid pyrophosphate (SAPP) or sodium hexametaphosphate (SHMP) for its effect on chemical traits, sensory characteristics, storage life or visual properties of restructured beef steaks. The objective of this study was to determine the effects of three phosphates (STP, SHMP, SAPP) on chemical, sensory, visual traits and storage life of restructured beef steaks formulated from lean bullocks.…”
Section: Introductionmentioning
confidence: 99%